History of Physical Teen Dating Violence and Its Association With Suicidal Behaviors Among Adolescent High School Students: Results From the 2015 Youth Risk Behavior Survey. Issue 17 (September 2021) - Baiden, Philip; Mengo, Cecilia; Small, Eusebius
Although studies have investigated and found physical teen dating violence (TDV) has a significant negative impact on mental health outcomes, few studies are yet to investigate the effect of physical TDV on suicidal behaviors among adolescents. The objectives of this study are to examine the prevalence of physical TDV, suicidal ideation, suicide plan, and suicide attempt among adolescents aged 14 to 18 years and the association between physical TDV and these suicidal behaviors. Data for this study were obtained from the 2015 Youth Risk Behavior Survey. A sample of 9, 693 adolescents aged 14 to 18 years (50.4% males) was analyzed using logistic regression with suicidal ideation, suicide plan, and suicide attempt as outcome variables and physical TDV as the main explanatory variable. About 17% of the adolescent students experienced suicidal ideation, 13.7% made a suicide plan, and 7.6% attempted suicide during the past 12 months. Among those who were dating, 9.9% experienced physical TDV. In the multivariate logistic regression, adolescent students who experienced physical TDV were 1.92 times more likely to have experienced suicidal ideation, 1.67 times more likely to have made a suicide plan, and 2.42 times more likely to have attempted suicide during the past 12 months when compared with their counterparts who were dating but experienced no physical TDV. Other significant predictors of suicidal behaviors include being a sexual minority, experiencing forced sex, bullying, feeling sad or hopeless, and binge drinking. Having sufficient sleep lowered the odds of suicidal ideation and suicide plan. The topic of physical TDV and its association with suicidal behaviors among adolescents is such an important issue for researchers, policymakers, and practitioners in the United States and around the world. Prevention and intervention efforts should be culturally tailored to reflect the unique experiences with physical TDV and suicide among minority populations such as sexual minority adolescents.